2010
DOI: 10.1159/000314495
|View full text |Cite
|
Sign up to set email alerts
|

Significance of MRI in Diagnosis and Differential Diagnosis of Parkinson’s Disease

Abstract: The differential diagnosis of parkinsonian syndromes is considered one of the most challenging in neurology, even for movement disorder specialists. Despite published consensus operational criteria for the diagnosis of Parkinson’s disease (PD) and the various atypical parkinsonian disorders (APDs) such as progressive supranuclear palsy, multiple system atrophy, and corticobasal syndrome, the clinical separation of APDs from PD carries a high rate of misdiagnosis. However, an early differentiation between APD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
138
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 288 publications
2
138
0
2
Order By: Relevance
“…These findings expand the previously known results of conventional and diffusion-weighted MRI [6,34,35,36,37]. In a recent DTI study in PSP, metrics of the CC and superior cerebellar peduncles were found to be the best predictors of global disease severity scale scores [38]; here, an alternative postprocessing cascade was used, estimating the diffusion tensor using the DTIfit toolbox (http://www.fmrib.ox.ac.uk/fsl/).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings expand the previously known results of conventional and diffusion-weighted MRI [6,34,35,36,37]. In a recent DTI study in PSP, metrics of the CC and superior cerebellar peduncles were found to be the best predictors of global disease severity scale scores [38]; here, an alternative postprocessing cascade was used, estimating the diffusion tensor using the DTIfit toolbox (http://www.fmrib.ox.ac.uk/fsl/).…”
Section: Discussionsupporting
confidence: 90%
“…a ‘classical' presentation classified as Richardson's syndrome (PSP-RS) and a subtype characterized by a more Parkinson's disease (PD)-like presentation in the early disease course classified as PSP-parkinsonism (PSP-P) [4]. In the diagnostic workup, magnetic resonance imaging (MRI) signs of PSP include prominent midbrain and pons atrophy, which have been combined in the conventional MR parkinsonism index [5,6]. Volumetric/morphometric MRI studies have shown frontal atrophy in PSP [7,8] and have demonstrated tissue loss in fronto-/mesiotemporal cortices and prefrontal regions in addition to the central midbrain and basal ganglia [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mahlknecht et al [22] offer an updated overview of MRI-based methods for the differentiation of PD and AP. Characteristic differences of regional ADC and FA values between PD and MSAp patients as well as compared to healthy controls have been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…First, abnormalities that have been validated for the evaluation of parkinsonian syndromes were scored. [3][4][5]25 Second, selected abnormalities were grouped in a score typical for a given disease. Atrophy and T2 hypointensity changes of the putamen, pontine atrophy, hot cross bun sign, cerebellar atrophy, and T2 hyperintense signal changes of the middle cerebellar peduncle were combined in the "MSA" score.…”
Section: Imaging Analysismentioning
confidence: 99%
“…[3][4][5] New MR imaging techniques have become available for clinical practice in recent years, including susceptibility-weighted imaging. SWI is sensitive to magnetic susceptibility differences in tissues such as blood, calcification, and iron deposition.…”
mentioning
confidence: 99%